Teaching Strategies During the COVID-19 Pandemic: Tailoring Virtual Learning for Public Health and Cancer Health Disparities Education - Moralez, Ernesto A.; Boren, Rachel L.; Lebel, Deanna L.; Drennan, Marilyn; Olvera, Destiny R.; Thompson, Beti (Frontiers in Public Health, 2022)
The COVID-19 pandemic has dramatically impacted higher education institutions in the United States (US). Given the dangers of close social interaction in spreading COVID-19, colleges and universities closed their campuses to minimize and often restrict face-to-face instruction of any kind, including supplemental skill development training and experiential learning. In exchange, higher education institutions implemented online learning strategies to continue education for students, including in-person experiential field experiences. This paper describes the adaptation of an in-person experiential field experience into an eight-day virtual workshop as a result of COVID-19 restrictions along with results from participant surveys evaluating pre-and post-test changes in knowledge and their overall assessment of the virtual workshop. This workshop, the Public Health and Cancer Research Workshop (PHCRW), was tailored for students from health-related graduate programs with the primary goal of introducing students to the causes and impacts of cancer disparities in the US/Mexico border region and research related to mitigating those disparities. The course facilitators added a professional development curriculum necessary for student success and the pursuit of advanced degrees such as academic/job interviewing skills and scientific and grant writing. The objectives were for students to (1) understand introductory and intermediate curriculum on public health, cancer, and cancer research; (2) examine the interrelationships among factors impacting public health problems; (3) describe the components of the research process; (4) describe various components of scientific writing; and (5) demonstrate professional strategies associated with school admission and employment. Students completed pre-and post- self-assessments that indicated gains in knowledge about cancer topics, particularly cancer prevention strategies (Mpre = 3.43; Mpost = 4.43), social determinants associated with cancer (Mpre = 3.29; Mpost = 4.43), and cancer rates by characteristics (Mpre = 3.43; Mpost = 4.43). Additionally, students overwhelmingly stated that they appreciated the opportunity to supplement their educational experience in a virtual format. Though the virtual format proved challenging in some respects, students expressed high satisfaction with the workshop. In addition to achieving the goals, the workshop successfully increased students’ skills, knowledge, and self-confidence. Despite the last-minute adaptation of the PHCRW, students’ satisfaction indicated that this program was an overall success.